Product-Marketing Innovation, Skills, and Firm Productivity Growth - Martin Junge; Battista Severgnini; Anders Sørensen (Copenhagen Business School (CBS), Department of Economics, 2012)
The role of product and marketing innovation for productivity growth is addressed using survey and register data for the Danish economy. It is argued that marketing and product innovation are complementary inputs and that innovation activities are skill-intensive. It is found that product and marketing innovation in skill-intensive firms results in significantly faster productivity growth than in unskilled-intensive firms that introduce this combination of innovation activities. More precisely, an increase in the share of educated workers of one percentage point, increases productivity growth by around 0.1 percentage point in firms with product and marketing innovation. In addition, it is found that firms that engage in product innovation but not in marketing innovation or the other way around do not demonstrate a growth effect from their innovation activities. It is also found that product and marketing innovation has an independent role in productivity growth that cannot be attributed to organisational changes, even though the majority of innovative firms engage in this latter innovation type.
hdl:10398/8468
Keywords: J24; M31; O31; 330; product innovation; marketing innovation; organizational innovation; productivity growth; educational composition